Design and Simulation of Microbolometer with Dual Cavity for High Figure of Merits - Kevin O. Díaz Aponte; Yanan Xu; Mukti Rana (Micromachines, 2023)
The rapid expansion of the applications of infrared (IR) sensing in the commercial market has driven the need to develop new materials and detector designs for enhanced performance. In this work, we describe the design of a microbolometer that uses two cavities to suspend two layers (sensing and absorber). Here, we implemented the finite element method (FEM) from COMSOL Multiphysics to design the microbolometer. We varied the layout, thickness, and dimensions (width and length) of different layers one at a time to study the heat transfer effect for obtaining the maximum figure of merit. This work reports the design, simulation, and performance analysis of the figure of merit of a microbolometer that uses GexSiySnzOr thin films as the sensing layer. From our design, we obtained an effective thermal conductance of <semantics>1.0135×10−7 W/K</semantics>, a time constant of <semantics>11 ms</semantics>, responsivity of <semantics>5.040×105 V/W</semantics>, and detectivity of <semantics>9.357×107 cm−Hz1/2/W</semantics> considering a <semantics>2 μA</semantics> bias current.